Pengaruh Sensori Integration Dan Isotonic Exercise Terhadap Peningkatan Kekuatan Otot Pada Anak Down Syndrome - Diki Ananda; Roy Daniel Nainggolan; Yeni Vera (Jurnal Kesehatan dan Fisioterapi, 2022)
Background: Down syndrome is a genetic disorder and complex growth and development disorders due to abnormalities during chromosomal division. Finally, this condition hampers the development and ability of daily activities. Sensory integration and Isotonic exercise are intended as interventions in increasing muscle strength and motor abilities in children with Down syndrome. Objectives: The purpose of this study is to determine whether or not there is an effect of Sensory integration and Isotonic exercise on increasing muscle strength in children with Down syndrome at the therapy service center. Kanaya, Siak Regency. Methods: This study uses a quasi-experimental research design with "One group Pretest-Posttest". The sampling technique used is total sampling by taking 12 samples of children with Down syndrome at the Kanaya Therapy Service Center, Siak Regency. The data that has been collected will be analyzed univariately and bivariately. Results: The results of this study are that there is an increase in muscle strength in children with Down syndrome after and after giving Sensory integration and Isotonic exercise. <0.05) which means that the hypothesis (Ha) is accepted. Conclusion: There is an effect of providing Sensory integration and Isotonic exercise on increasing muscle strength in children with Down syndrome at the Kanaya Therapy Service Center, Siak Regency..Keywords: Improvements, strength, Muscles, Distractions